PENGENALAN ISTILAH KULINER PRANCIS PADA SISWA SMK N 3 KENDARI PROGRAM TATA BOGA - Samsul Samsul; Yuli Mahmudah Sentana; Muh. Yazid A.R.G (Seshiski: Southeast Journal of Language and Literary Studies, 2022)
As the world center of culinary, it is not only French food that is global but also its cutting and dicing techniques and French cooking terms.These French culinary terms that have became worldwide in tourims make culinary industry have no choice but to embrace it. As a tourism school, SMKN 3 Kendari must participate on studying it so that its graduates will have the skill that the world need. However, the absence of a French teacher is a problem for SMKN 3 Kendari. Thus, a training was carried out as a learning effort for students, especially for culinary student. This training is not only aiming to increase students' knowledge of French culinary terms but also to make students to be able to pronounce French culinary terms correctly. So that later these skills can be useful for them in the working world.